Performance validation of microchannel heat sinks based on single/multiobjective topology optimization and manufactured by selective laser melting - Guangzhao Yang; Mingxuan Cao; Pingnan Huang; Linlin Pan; Xin Zhong; Liang Yang; Weiwei Guo; Matthew M.F. Yuen; Huijun Li (Case Studies in Thermal Engineering)
This study presents the design and experimental validation of two-dimensional (2D) and pseudo three-dimensional (P3D) microchannel heat sinks optimized through single-objective and multiobjective topology optimization via the solid isotropic material with penalization (SIMP) method. The optimization objectives were to maximize the heat transfer efficiency and minimize the pressure drop, aiming for a balanced thermal performance. Microchannel heat sinks were fabricated via selective laser melting (SLM), and thermal performance and flow resistance were measured. The results showed that the P3D multiobjective topology optimization model (P3D-MOTO) is superior to other models. When the flow rate increased from 20 ml/min to 80 ml/min, P3D-MOTO significantly reduced the temperature by 8.9 °C while maintaining a low pressure drop, demonstrating excellent performance. Compared with conventional microchannel heat sinks, the P3D-MOTO is 10.3 °C cooler at high flow rates and offers an optimal balance between increased heat transfer efficiency and reduced flow resistance. The performance evaluation criterion (PEC) value of P3D-MOTO increased from 1.19 to 1.46 as the flow rate increased, indicating superior overall performance. This study confirms that the P3D-MOTO provides efficient and energy-saving thermal management solutions, while emphasizing that the integration of topology optimization with SLM can create complex geometries, thereby enhancing thermal performance.